Resistance screening and in silico characterization of cloned novel RGA from multi-race resistant lentil germplasm against Fusarium wilt (Fusarium oxysporum f. sp. lentis) - Nishmitha, K.; Singh, Rakesh; Dubey, Sunil C.; Akthar, Jameel; Tripathi, Kuldeep; Kamil, Deeba (Frontiers in Plant Science, 2023)
Fusarium wilt caused by Fusarium oxysporum f. sp. lentis (Fol) is the most devastating disease of lentil present worldwide. Identification of multi-race fusarium wilt resistance genes and their incorporation into existing cultivars will help to reduce yield loss. In the present study, a hundred lentil germplasm belonging to seven lentil species were screened against seven prevalent races of Fol and accession IC201561(Lens culinaris subsp. culinaris), EC714243 (L. c. subsp. odemensis) and EC718238(L. nigricans) were identified resistant. The typical R gene codes for the nucleotide-binding site and leucine-rich repeats (NBS-LRR) at the C terminal linked to either Toll/interleukin 1- like receptor (TIR) or coiled-coil (CC) at the N terminal. In the present study degenerate primers designed from the NBS region amplifying P-loop to GLPLA motif isolated forty-five resistance gene analogues (RGA) from identified resistant accessions. The sequence alignment identified both classes of RGA, TIR and non-TIR based on the presence of Aspartate (D) and Tryptophan (W) at the end of kinase motif respectively. The phylogenetic analysis grouped RGA into six classes, LRGA1 to LRGA6 determining the diversity of RGA present in the host. Grouping of RGA identified from Lens nigricans, LnRGA 2, 9, 13 with I2 reveals the structural similarity with the fusarium resistance gene. The similarity index ranged fromof 27.85% to 86.98% was found among RGA and from 26.83% to 49.41% amongbetween known R genes, I2, Gpa2, M and L6. Active binding sites present along the conserved motifs have grouped the RGA into 13 groups. ADP/ATP being the potential ligand determines ATP binding and ATP hydrolysis activity of RGA. The isolated RGA can be used in developing markers linked to the functional R gene. Further, expression analysis and full-length gene isolation pave the path to identifying the molecular mechanism involved in resistance.